(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
The results of studies on the justification of design solutions ensure reliable designs at progressive collapse were presented. Analysis of the stress-strain state of the structures was performed using software package «Lira 9.6». The most effective amount of stiffening diaphragms to ensure the reliability of the building was determined. The features of the impact on the reliability of the floor structure of the building was determined. The results of evaluation of the stability of columns of different types to explosive impact were presented. Keywords: progressive collapse, reliability, reinforced concrete structures, composite structures, columns, diaphragm stiffness, finite element method.